Control of Excited‐State Conformations in B, N‐Acenes. Issue 13 (20th February 2019) - Lu, Zhenpin; Quanz, Henrik; Ruhl, Julia; Albrecht, Georg; Logemann, Christian; Schlettwein, Derck; Schreiner, Peter R.; Wegner, Hermann A.
Abstract: We present a new concept to control the conformations of molecules in the excited state through harvesting negative hyperconjugation. The strategy was realized with the 2, 3, 1, 4‐benzodiazadiborinane scaffold, which was prepared by a new synthetic procedure. Photochemical studies identified dual light emission, which was assigned to well‐defined conformers. The emission at longer wavelength can be switched off by restricting the rotational degrees of freedom in the solid state as well as by controlling the energy levels of the excited states through adjusting the solvent polarity. Abstract : The conformation of molecules in the excited state can be controlled through harvesting negative hyperconjugation, as exemplified for a (B‐N)2 ‐acene, for which a new synthetic procedure was developed. The resulting dual fluorescence can be switched off by restricting the rotational degrees of freedom or by controlling the energy level of the excited state by adjusting the solvent polarity.